2009
DOI: 10.1007/s10534-009-9284-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage to DNA by 1,10-phenanthroline/l-threonine copper (II) complexes with chlorogenic acid

Abstract: The oxidative DNA damage by copper (II) complexes in the presence of chlorogenic acid was explored using agarose gel electrophoresis. The extent of pBR322 DNA damage was enhanced significantly with increasing concentration of [Cu-phen-Thr] complex and incubation time. A fluorescence quenching activity of calf thymus DNA-EB was observed more remarkably with chlorogenic acid than without chlorogenic acid. The fluorescence measurements suggested that [Cu-phen-Thr] complex not only can bind to DNA by intercalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The quenching constants were comparable to the values reported for [Cu-Phen-Thr] complex (K sv = 15.63 9 10 4 M -1 ). The result explained that [Cu-Phen-Tyr] complex has a stronger affinity than [Cu-Phen-Thr] complex (Wang et al 2010), this resulted from L-tyrosine contained aromatic structure. The fluorescence titration data were analyzed to construct the binding curves, and from these curves, binding constants as well as binding site sizes were estimated.…”
Section: Fluorescence Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The quenching constants were comparable to the values reported for [Cu-Phen-Thr] complex (K sv = 15.63 9 10 4 M -1 ). The result explained that [Cu-Phen-Tyr] complex has a stronger affinity than [Cu-Phen-Thr] complex (Wang et al 2010), this resulted from L-tyrosine contained aromatic structure. The fluorescence titration data were analyzed to construct the binding curves, and from these curves, binding constants as well as binding site sizes were estimated.…”
Section: Fluorescence Studiesmentioning
confidence: 97%
“…Recent report from our laboratory has shown that 1, 10-phenanthroline/Lthreonine copper (II) complexes with chlorogenic acid as biological reductant can induce DNA oxidative damage (Wang et al 2010). Gallic acid (GA), a naturally occurring plant phenol, was also found to be a strong antioxidant in emulsion or lipid systems (Hirose et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in accordance with studies that have indicated that higher levels of reactive oxygen species have a destructive effect on DNA and some proteins and that the associated oxidative stress can trigger apoptosis (Simon et al 2000;Sandstrom et al 1994). It is particularly interesting, that the aliphatic 1,4-dithiane complex 14 induced high ROS concentrations similar to those of complex 8, although it does not contain an aromatic diimino donor ligand, whose abilitiy to invoke ROS through either irradiation or through reactions with cellular reductants is well-documented (Levina et al 2009;Wang et al 2010).…”
Section: Measurements Of Reactive Oxygen Species (Ros)mentioning
confidence: 99%
“…However, a very few copper carboxylates have been reported so far with alpha glucosidase, acetylcholine and butyrylcholine esterases inhibition activity. [22][23][24][25] Since enzyme targeting is potential therapy in modern era of medicinal research therefore combining an essential metal and two different organic ligands together in a single molecule to develop lifesaving drugs could be attractive solution. Organic ligands in these complexes affect and regulate their activity by neutralizing the charge on copper ion and facilitating the transport across the cell membranes.…”
Section: Introductionmentioning
confidence: 99%